Can someone help me with this question...im so lost...thanks in advance...
If X has the geometric distribution with parameter p, show that
P(X > m + n | X > m) = P(X > n).
Hello,
Well, note that $\displaystyle P(X>k)=\sum_{j=k+1}^\infty (1-p)p^j$
And then just write that $\displaystyle P(X>m+n|X>m)=\frac{P(X>m+n,X>m)}{P(X>m)}=\frac{P(X >m+n)}{P(X>m)}$
because if X>m+n happens, X>m happens too.
try the following link for some explanation memoryless property of geometric distribution
mean and variance of the geometric distribution